Genome-wide association studies reveal novel QTLs for agronomic traits in soybean - Han, Dongwei; Zhao, Xi; Zhang, Di; Wang, Zhen; Zhu, Zhijia; Sun, Haoyue; Qu, Zhongcheng; Wang, Lianxia; Liu, Zhangxiong; Zhu, Xu; Yuan, Ming (Frontiers in Plant Science, 2024)
Introduction Soybean, as a globally significant crop, has garnered substantial attention due to its agricultural importance. The utilization of molecular approaches to enhance grain yield in soybean has gained popularity. Methods In this study, we conducted a genome-wide association study (GWAS) using 156 Chinese soybean accessions over a two-year period. We employed the general linear model (GLM) and the mixed linear model (MLM) to analyze three agronomic traits: pod number, grain number, and grain weight. Results Our findings revealed significant associations between qgPNpP-98, qgGNpP-89 and qgHGW-85 QTLs and pod number, grain number, and grain weight, respectively. These QTLs were identified on chromosome 16, a region spanning 413171bp exhibited associations with all three traits. Discussion These QTL markers identified in this study hold potential for improving yield and agronomic traits through marker-assisted selection and genomic selection in breeding programs.